(untitled) (American Journal of Islam and Society, 2012)
Black Mecca undoubtedly is a new contribution to the literature on Islam in America. It contributes to a better understanding of African Muslim immigrants in the United States. Only a few books have been published on African immigrants in the United States, and Black Mecca definitely adds a new dimension to the discussions of African immigrant roles in the United States and to Islamic thought in general. This work will allow readers to recognize that West African Muslims are not just earning incomeh in the United States; they are actually contributing to the development of Harlem in New York. Often times, many immigrants would reside in low-class residences until they become affluent, then they would leave the area. These African Muslims consider Harlem their home; they have turned it into a thriving business area; they reside there and develop it by building schools and mosques for their community ...